Are You There, Crocodile? : Inventing Anton Chekhov. - Pennington, Michael (Oberon Books, 2016)
Michael Pennington's work on his solo show about Anton Chekhov has taken London's 'Russian Actor' from the Trans-Siberian Railway to Soviet and post-Soviet Moscow, into the repertoires of the National Theatre and the Old Vic and across Europe. Are You There, Crocodile' also includes accounts of his work on Dostoevsky's Crime and Punishment, Tolstoy's Strider and other Russian projects, as well as searching essays on how Chekhov's four masterpieces actually work in the theatre. This book is a study of the great writer, a partial autobiography, and, centrally, an actor's search for identification with the elusive Anton Chekhov himself.